Study of water droplet impinging on surface - Nishita Sasi (Nanyang Technological University, 2020)
This report presents an investigation of the maximum spreading diameter of water droplets after impinging on aluminium surfaces. Droplet impingement has been studied over the years and it has yielded many beneficial applications such as spray cooling and anti-icing. The dynamic process occurs within a short period, thus making it invisible to the eye. Therefore, there is a need for a high-speed camera to further examine the impingement in greater detail. The impact process was captured with a Phantom V711 digital high-speed camera, which has the ability to capture up to a million frames per second. The high-speed camera is able to provide a vast range of high resolution images, which in turn enables researchers to analyse and understand the characteristics of the water droplets’ developments as it impacted the surface. In this study, the three highly influential parameters for the experiment are: (1) the type of aluminium surface, (2) droplet release height and (3) the temperatures of the surface. The videos would then be obtained and meticulously processed and analysed through the use of ImageJ software. The effects of these parameters on the spreading diameters were compared and analyzed. In addition to the analysis, previous studies on the dynamic nature of water droplet impingement are included in separate sections to provide a methodical flow and coherent comprehension of the study.